(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This research paper examines the multifaceted relationship between technology and language acquisition. With the rapid advancement of technology, particularly in the realm of digital media and communication devices, the way individuals acquire and interact with languages has undergone significant transformations. This paper delves into the various ways technology impacts language acquisition, encompassing both positive and negative influences. Drawing on a wide range of empirical studies, theoretical frameworks, and real-world examples, this research provides insights into how technology shapes language learning processes, educational practices, and linguistic outcomes. Additionally, it explores the implications of these findings for educators, policymakers, and individuals engaged in language learning endeavors.